Meningkatnya Moderasi Beragama di Lingkungan Warga Sekolah: Studi Pendidikan Moderat di SD Negeri 4 Klungkung - Bhandesa, Asthadi Mahendra; Sutrisna, I Putu Gede; Kartiningsih, NLP; Mahayati, Tuti Suryatini (Cetta: Jurnal Ilmu Pendidikan, 2024)
The religion moderation contains an understanding in a commendable attitude that is built on a positive understanding of religious teachings, in the form of thoughts, words and actions that lead a person to a not-extreme behaviour in responding to things and has a complete attitude of tolerance. The purpose of this research was to analyze the implementation of religion moderation in the school and its benefits for the school environtment. This study was employed a qualitative research, with a grounded theory approach. The data was collected using interview and observation techniques, and other supporting documents. The research indicated that (1) Religion moderation was a comprehensive understanding that was in harmony with and built on religious teachings, implemented in the form of thoughts, words and actions by emphasizing overall tolerance in relations with and between religious communities, (2) Implementation of religion moderation in the Public Elementary School 4 Klungkung was carried out by prioritizing aspects of harmony, mutual respect, mutual support formal activities in the both classroom and outside the classroom such as greeting all religious communities, giving greetings and support to each other religious holidays , and holding a dharma santhi activities at the end of each school year, (3) the benefits of implementing religion moderation at school were in the form of comfort for every school member, lively activities on religious days, and an increase in mutual respect and love between school members.